Impact of ice formations on the shore and bottom areas of shallow seas and large lakes of middle and subarctic latitudes - S. V. Maznev; S. A. Ogorodov (Лëд и снег)
Ice formations affect linear and coastal structures not only in the Arctic, but also in the subarctic and middle latitudes. Most of the seas, lakes and bays, such as the Gulf of St. Lawrence, the Baltic, Black, Caspian Seas, and Sea of Japan, freeze partially or completely every year. Inland and northern lakes and seas of the Subarctic, such as the White Sea, the Gulf of Bothnia and the Sea of Okhotsk are characterized by the most severe ice conditions. Remote sensing methods are used to detect ice ridges and grounded hummocks. A side-scan sonar survey and echo sounding, along with the diving surveys, are used to detect the ice scours/furrows on the bottom. To study the ice-exaration relief on the exposed bottoms, remote sensing data and materials obtained by means of unmanned aerial vehicles (UAV) are used, along with field surveys. The pressure impact of ice on the land results in the formation of ice piles on shores up to 3–5 m high. This causes an intensification of the processes of destruction of the coast and the restructuring of the processes of relief formation. The ice pressure ridges up to 2–3 m high are widely distributed along the coasts. At the bottoms, typical ice scours (plowing furrows) have a dip along the central axis, as well as side and pressure rollers at the ends of the furrows. At the edge of the fast ice, multiple scours/furrows form a so-called «comb», usually oriented along the normal to the shoreline. The length of the largest furrows exceeds several kilometers; the width of individual ones reaches the first tens of meters, the systems of furrows - hundreds of meters; the depth of them can be down to 2 m. The maximal depth of the sea or lake at which impacts are possible can reach 30 m. Relic forms of ice and iceberg impact have also been studied in the middle latitudes. Traces of impacts of ice formations in the temperate zone have a low degree of preservation and are often concealed by sediments. The distribution of traces of ice impacts down to a depth of 30 m as well as to several hundred meters inland shows the scale of the process in temperate and subarctic climates. Ice heaps and thrusts are more common in mid-latitudes than in the Arctic.